Effects of Free Amino Acids, Metallothionein, and Chemical Forms of Heavy Metals on the Accumulation and Detoxification of Cadmium and Chromium in Chinese Goldthread (Coptis chinensis Franch.). (6th October 2022) - Huang, Wenli; Niu, Yuting; Li, Yuze; Zhang, Dongdong; Jiang, Yi; Zhang, Huawei; Deng, Chong; Yang, Xinjie; Wang, Wei; Song, Xiaomei; Ding, Meihai; Liang, Zongsuo
Abstract : Chinese goldthread ( Coptis chinensis Franch.) is an important medicinal plant worldwide. However, its clinical safety is negatively impacted by high cadmium (Cd) and chromium (Cr) levels. Understanding the accumulation pattern and detoxification mechanism of heavy metals, such as Cd and Cr, is important for regulating their transportation and reducing their accumulation in plants. Free amino acids (FAAs), metallothioneins, and chemical forms of heavy metals are closely associated with heavy metal accumulation and detoxification mechanisms. In the present study, we evaluated the uptake of Cd and Cr in Chinese goldthread and characterized the changes in FAA levels, CcMT2, a metallothionein gene, expression under Cd and Cr stress, and Cr chemical forms in various tissues of Chinese goldthread. The majority of Cd and Cr was retained in the roots; this might be the tolerance strategy utilized by Chinese goldthread to protect the aboveground photosynthetic tissues. A chemical continuous extraction method was utilized to analyze the chemical forms of Cr, and the results suggested that Cr was primarily fixed by oxalate in all tissues, and after Cr treatment, Cr tended to combine with phosphate to form an insoluble complex that reduced the toxicity and bioavailability of Cr in Chinese goldthread. The accumulation of Cd and Cr was significantly positively correlated with valine, histidine, threonine, tyrosine, and serine levels and significantly negatively correlated with glutamic acid and alanine levels. The variation in proline levels under Cd stress was different than that under Cr stress. FAAs might affect the accumulation of and resistance to Cd and Cr through various detoxification strategies, such as chelation with heavy metals ions and conversion into the required products. Furthermore, CcMT2 was isolated for the first time and found to be dominantly expressed in leaves. CcMT2 was induced under Cd and Cr stress in all plant tissues, indicating its role in the accumulation of and tolerance to Cd and Cr.